2000
DOI: 10.1021/ma991113+
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of the Small-Angle X-ray Scattering from Swollen and Oriented Perfluorinated Ionomer Membranes

Abstract: Small-angle X-ray scattering (SAXS) and bulk volumetric measurements were performed on the perfluorinated ionomer membrane "Nafion". The swelling experiments were conducted using controlled environments of different relative humidities. The membranes were oriented using uniaxial draw, both before and after conversion of the precursor material, as well as both sequential and simultaneous biaxial draw. Using a novel model-independent maximum entropy method, it is shown that the most statistically probable scatte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
197
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(213 citation statements)
references
References 15 publications
15
197
0
1
Order By: Relevance
“…The corresponding flexure goes through a maximum with time [37]. Macroscopic swelling, also referred to as bulk swelling, is defined as the large-scale expansion of ionomer membranes in an area of at least 1 mm 2 [40]. It is well known that the character of a PEM is depending on the solvent used for membrane casting [19].…”
Section: Surface Behavior Of Copolymer Speek-hq Membranementioning
confidence: 99%
“…The corresponding flexure goes through a maximum with time [37]. Macroscopic swelling, also referred to as bulk swelling, is defined as the large-scale expansion of ionomer membranes in an area of at least 1 mm 2 [40]. It is well known that the character of a PEM is depending on the solvent used for membrane casting [19].…”
Section: Surface Behavior Of Copolymer Speek-hq Membranementioning
confidence: 99%
“…On a longer length-scale, the inhomogeneous distribution of the ionic groups, and the pretreatment of Nafion, often by extrusion, have their impact. Regions of Fluorocarbon backbone with low ionic density may crystallize, forming a stiff scaffolding which provides the elastic structure within which the water and the higher ionic content, uncrystallized polymer phase-separate [39,40]. The crystalline network occupies the 10-20 nm length-scale, often refereed to as the "matrix knee" [6].…”
Section: A Study Of Nafion: Comparison To Saxs Datamentioning
confidence: 99%
“…There has been controversy regarding the morphology of the water network as numerical and experimental investigation of the microstructure of Nafion and related PFSA membanes have lead to the proposition of bi-layer morphologies [42,43], cylindrical pores [44], an inverted pore morphology with solvent groups surrounding cylinders of crystallized backbone [6,45], spherical clusters [39], as well as more complex morphologies suggested by atomistic simulations [3,35,46,47]. Regarding the crystalline domains, proposed models include lamellar models [48], the rod-like model [45], a fringed-micelle model [40], and bi-modal networks [49].…”
Section: A Study Of Nafion: Comparison To Saxs Datamentioning
confidence: 99%
“…These phenomena are critical for high membrane proton conductivity and high PEMFC power density. 15,16 A wealth of analytical techniques has been used to obtain morphological and structural information about Nafion  , including X-ray and neutron scattering, 13,14,[17][18][19][20][21][22] electron microscopy, 23 atomic force microscopy (AFM), [24][25][26][27][28][29] numerical modeling, 30,31 etc. Numerous studies of the ionic conductivity of Nafion ® have been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%